ANALISIS PENGELOLAAN AGRIBISNIS PETANI HORTIKULTURA STUDI KASUS : KABUPATEN ASAHAN - Gustami Harahap (JURNAL AGRICA, 2017)
This study aims to determine the management of agribusiness horticulture farmers in the District Asahan. Research method using library research method. This research uses literature review method (library research). The discussion in this paper is based on statistical data obtained from BPS from various research results related to the management of agribusiness. From the discussion it can be concluded that the planning of horticultural commodities agribusiness: vegetables and fruits associated with the demand for commodities what the market needs gradually increasingly sensitive farmers, evidenced by the cultivation of new commodities of mushrooms from 2011 to 2012. Farmers have not monitoring the properties of horticultural commodity products: vegetables and fruits more effectively and efficiently, due to the fact that farmers are limited to post-harvest technology knowledge, so they tend to sell their commodities more quickly. Organizing sources of labor production factors in the family consisting of: (husband, wife and children) full of work in cultivating horticultural commodities of vegetables and fruits, has not been calculated as a sacrifice of production costs, because the farmers have not recorded in the bookkeeping of his farm . KUD as a supporting institution in increasing the income of farmers, can not be regarded as a pillar of the economy, due to lack of awareness of farmers to become members of the KUD, evidenced there are still a lot of farmer groups (Gapoktan) horticulture that do not have KUD institutions